"Teacher’s classroom behaviour and subject mastery as correlates of students’ performance in Yoruba " (2013)
The study investigated Teacher's Classroom Behaviour and Subject Mastery as Correlates of Students' Performance in Yoruba. The study adopted a descriptive design. The population consisted of S.S.1I students and the Yoruba language teachers in public senior secondary schools in Ilesa East local Government, Osun State, Nigeria. The sample comprised eight hundred S.S. II students spread over eight our of the twenty four public senior secondary schools in the Local Government Area. All the twenty four (24) Yoruba language teacher teachers in the eight (8) sampled schools were also use for the study. Two instruments, constructed and validated for data collection were Teacher Classroom Behaviour Observation Scale (r = 0.72) and performance test in Yoruba language (r = 0.80). Data collected were analyzed using frequency counts, simple percentage and multiple regression analysis to test the formulated hypotheses. All the hypotheses were tested at 0.05 level of significance. The study showed that subject mastery of the teachers (P = 0.146; t = 4.611; p < 0.05) and teachers’ classroom behaviour (P = 0.0102; t = 3.112; p < 0.05) related significantly with students’ performance in Yoruba language. There is a significant composite effect of teacher’s subject mastery, classroom behaviour, teaching experience and teachers’ qualification on the academic performance of students in Yoruba language (F (4j825) = 10.241, P < 0.05). Hence teachers’ attitude to work relate significantly to the students’ academic performance in Yoivba (Adjusted R2 = 0.039). Based on the findings, it was recommended that qualified and experienced Yoruba language teachers should be made to handle Yoruba language teaching especially in senior secondary schools. In addition, teachers should be exposed to in-service training to increase their knowledge and skills in the teaching profession